Maternal serum triglyceride at midpregnancy and newborn weight in nondiabetic and normal BMI women - Sekhavat, Leila; Zare, Fatemah; Karbasi, Sedighah Akhavan (Nepal Journal of Obstetrics and Gynaecology, 2008)
Aim: To determine whether elevated midpregnancy (24 -28 Gestational weeks) maternal serum lipid levels predict the risk of macrosomia in non-diabetic women. Methods: Nondiabetic pregnant women (who had negative diabetic screens) were enrolled. Fasting serum triglyceride, and total cholesterol levels were measured at 24-28 weeks gestation. We tested the association between maternal variables and birth weight by univariable analysis. We also used multiple logistic regression analysis to determine whether maternal hyperlipidemia is a risk factor for having an LGA infant. Results: We enrolled 190 subjects. Among measured maternal lipids, only triglyceride levels correlated with birth weight in univariable analysis (r2 = 0.40, P = .000). Logistic regression analysis showed that fasting maternal hypertriglyceridemia was the significant predictor of macrosomia, independent of maternal weight gain and fasting plasma glucose levels. (Odds ratio 11.2; 95% confidence interval 1.5, 31.2; P = .01). Conclusion: In nondiabetic women, fasting triglyceride levels at midpregnancy correlated positively with newborn weight at term. Keywords: Birth weight, hypertriglyceridemia, nondiabeic pregnant, normal BMI doi:10.3126/njog.v3i1.1434 NJOG 2008 May-June; 3(1): 19 - 23